Brain Cortical and Hippocampal Dopamine: A New Mechanistic Approach for Eurycoma longifolia Well-Known Aphrodisiac Activity and Its Chemical Characterization. (2nd June 2019) - Ezzat, Shahira M.; Ezzat, Marwa I.; Okba, Mona M.; Hassan, Salah M.; Alkorashy, Amgad I.; Karar, Mennatallah M.; Ahmed, Sherif H.; Mohamed, Shanaz O.
Abstract : Eurycoma longifolia Jack (Fam.: Simaroubaceae), known as Tongkat Ali (TA), has been known as a symbol of virility and sexual power for men. Metabolic profiling of the aqueous extract of E. longifolia (AEEL) using UPLC-MS/MS in both positive and negative modes allowed the identification of seventeen metabolites. The identified compounds were classified into four groups: quassinoids, alkaloids, triterpenes, and biphenylneolignans. AEEL is considered safe with oral LD50 cut-off >5000 mg/kg. Oral administration of 50, 100, 200, 400, or 800 mg/kg of AEEL for 10 consecutive days to Sprague-Dawley male rats caused significant reductions in mounting, intromission, and ejaculation latencies and increased penile erection index. AEEL increased total body weight and relative weights of seminal vesicles and prostate. Total and free serum testosterone and brain cortical and hippocampal dopamine content was significantly elevated in treated groups with no significant effects on serotonin or noradrenaline content.